MENINGKATKAN KINERJA MELALUI MOTIVASI PADA PEGAWAI RUMAH SAKIT UMUM DAERAH (RSUD) ANDI MAKKASAU DI KOTA PAREPARE - Perwira, Iwan (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2020)
This study aims to determine the effect of motivation (X) on the performance (Y) of employees of RSUD Andi Makkasau in the city of Parepare and to determine the indicators (physiological, job security, social, reward, self-actualization) of motivation (X) has a dominant effect on performance (Y) staff of Andi Makkasau Hospital in Parepare City. The research method used descriptive analysis and multiple linear regression analysis with a total of 60 respondents. The test results show that simultaneously Motivation (X) affects performance (Y) based on the coefficient of determination (R) and R square results. Partially, the indicators of needs that have the most dominant influence on performance (Y) are physiological (X1), followed by social (X3), appreciation (X4) then self-actualization (X5) and finally job security (X2)